Suppression of cutting forces using combined inverse model based disturbance observer and disturbance force observer - Madihah Maharof (2020)
This paper focuses on damping strategies that addressed the effect that high frequency harmonics content of cutting force have on positioning accuracy of the x-axis of an XY positioning table via controller and observer design approaches. Cutting force generated from direct contact between the workpiece and cutting tool becomes input disturbance to the drive system of the positioning table. The force high frequency components if left undamped would generate vibration to the system thus affecting the system positioning accuracy, surface finish quality as well as tool life. For this purpose, a cascade P/PI position controller, an Inverse Model Based Disturbance Observer (IMBDO) and a Disturbance Force Observer (DFO) were designed and numerically analysed. The cascade P/PI controller was designed using traditional loop shaping frequency domain method. IMBDO estimates the input disturbance and any unmodelled system dynamics while DFO performs direct estimation of the cutting force using knowledge of harmonic frequencies corresponding to the input cutting force. A combined cascade P/PI controller with IMBDO and DFO reduced additional 3.83% and 1.90% tracking errors compared to separate application of IMBDO and DFO. This novel control approach produced between 34-80% greater reductions in peak amplitudes of the harmonics content of the cutting forces compared to cascade P/PI.